A historical guide to Emily Dickinson - Pollak, Vivian R. (Historical guides to American authors., 2004)
One of America's most celebrated women, Emily Dickinson was virtually unpublished in her own time and unknown to the public at large. Today her poetry is commonly anthologized and widely praised for its precision, its intensity, its depth and beauty. Dickinson's life and work, however, remain in important ways mysterious. This collection of essays, all of them previously unpublished, represent the best of contemporary scholarship and points the way toward exciting new directions for the future. The volume includes a biographical essay that covers some of the major turning points in the poet's.